ANALISIS PENGELOLAAN DANA DESA DALAM PERSPEKTIF PERATURAN MENTERI DALAM NEGERI NOMOR 113 TAHUN 2014 DI DESA POLOBOGO , GETASAN KABUPATEN SEMARANG - ISNANTIYA SOFITRIANA; EKA RESMI HARTATI; NURIKA RIZKI AMALIA; MUAMMAR TAUFIQI LUTFI MUSTOFA; SAIFUL ANWAR (JURNAL EKONOMI, SOSIAL & HUMANIORA, 2020)
This study aims to analyze the management of village funds in Polobogo Village, Getasan Subdistrict, Semarang Regency, Central Java Province, and analyze the factors that hamper the management of village funds and efforts in overcoming the management of village funds. To achieve these objectives, qualitative research methods are used to parse the data descriptively. Data collection techniques are done by observation, interviews, and study of documents and archives using qualitative descriptive analysis techniques. Key information is determined by purposive sampling to get the right and fast information. The results showed that: (1) Management of village funds and utilization of village funds starting from planning, implementation, and reporting of accountability in Polobogo Village, Getasan District, Semarang Regency, Central Java Province, had referred to the Minister of Home Affairs No. 113 of 2014 concerning village financial management. (2) The factor of not well-implemented village financial management in Polobogo Village is the quality of human resources regarding the understanding of APBDes.